Islamic studies today : essays in honor of Andrew Rippin - Rippin, Andrew, 1950-; Daneshgar, Majid.; Saleh, Walid A. (Texts and Studies on the Qurʾān, 2017)
Islamic Studies Today: Essays in Honor of Andrew Rippin , is a collection of essays on the Qur'ān, qur'anic exegesis, the early history of Islam, the relationship of the qur'anic text to writings from other religious traditions, and the use of the Qur'ān in modern discussions and debates. Its scope is medieval and modern contexts and it covers regions right across the Muslim world. The essays are based on and reflect Rippin's broad interests and methodological innovations; his studies of text transmissions, hermeneutical studies of the Qur'ān; careful unpacking of the complex relations between qur'anic exegesis and historical contexts; and exploring potential new methodologies for future research. With contributions by: Herbert Berg, Stefano Bigliardi, Majid Daneshgar, Bruce Fudge, Claude Gilliot, Andreas Görke Feras Hamza, Gerald Hawting, Aaron W. Hughes, Tariq Jaffer, Marianna Klar, Jane McAuliffe, Arnold Yasin Mol, Angelika Neuwirth, Gordon Nickel, Johanna Pink, Michael E. Pregill, Gabriel S. Reynolds, Peter G. Riddell, Walid A. Saleh, Nicolai Sinai, Roberto Tottoli